Re- (creating a relaxing atmosphere in personal spaces) - Ho, Ping (2019)
The fast-changing world can be seen and felt evidently in Singapore through our ever-evolving landscapes and new advancements. Most of the world’s general population are stricken with a frantic lifestyle with long working hours where they spent majority of their time trapped inside of buildings repeatedly doing the same work or routines. This project is motivated by the curiosity of how product design can help to create a relaxing atmosphere in homes for users to unwind after a hard day. Nature was chosen as the methodology of this project because of the widening gap between man and the natural environment. However, taking into consideration that unfamiliar nature might end up frightening city-dwellers instead of having a relaxing effect on them, a familiar sight of nature was instead chosen as the inspiration of this project. Singapore is well-known for being a green city where rows of trees co-exist harmoniously with the built environment. Amongst these trees, the most commonly planted and seen is the Rain Tree. Therefore, rain trees are a familiar sight to all who stays in Singapore, even if they may or may not be able to identify them. This project tried to emulate the movement of a rain tree swaying in the wind as well as the dappled sunlight that filters through its canopy through a series of hanging paper lamps. Each of these lamps were made by hand, out of rice paper, and the freshly fallen leaves of the rain tree. Due to their lightness and their method of suspension, the hanging lamps oscillate gently in the presence of air currents, much like how the branches of the trees sway when the wind picks up. Ultimately, this project wishes to allow people to experience the relaxing effect of nature, hence helping them to unwind after a stressful and tiring day.